Method of Construction and Some Properties of 4-Row-Regular Circulant Partial Hadamard Matrices of Order \((k× 2k)\) - Manjhi, Pankaj Kumar (Communications in Mathematics and Applications, 2022)
In this paper, some properties of circulant partial Hadamard matrices of the form \(4-H(k× 2k)\) have been obtained together with a method of construction with the help of Toeplitz matrices.
Keywords: Hadamard matrices; Partial Hadamard matrices; Circulant partial Hadamard matrices; Toeplitz matrix; Orthogonal design